Return Saham pada Perusahaan yang Terdaftar di LQ45: Kajian Model Profitabilitas dan Rasio Pasar - Anastasya Priska Kusuma Dewi; Kristianingsih Kristianingsih; Koernia Purwihartuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) partially or simultaneously on stock returns in companies listed in the LQ45 index on the Indonesia Stock Exchange for the 2016-2020 period. This study uses associative and quantitative research methods. Based on the analysis of the research results, the conclusions are (1) partially Return On Assets has a significant negative effect of 0.008 on Stock Return, (2 ) partially Return On Equity has a significant positive effect of 0.026 on Stock Return, (3) partially Earning Per Share has no and insignificant effect on Stock Return and (4) Simultaneously Return On Assets, Return On Equity, and Earning Per Share has a significant positive effect on Stock Return, as indicated by the calculated F value of 2.814 and the coefficient of determination of 0.10.